Re‐evaluation of ammonium phosphatides (E 442) as a food additive. (9th November 2016) - ; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Domenico, Alessandro Di; Dusemund, Birgit; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Leblanc, Jean‐Charles; Lindtner, Oliver; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of ammonium phosphatides (E 442) as a food additive. The Scientific Committee on Food (SCF) and the Joint FAO/WHO Expert Committee on Food Additives (JECFA) allocated an acceptable daily intake (ADI) of 30 mg/kg body weight (bw) per day in 1978 and 1974, respectively. The Panel noted that after oral administration of E 442 ([ 32 P]YN), a proportion of the radioactivity passed through the gastrointestinal tract and was excreted via faeces and also a quantity of radioactivity was absorbed rapidly after dosing as indicated by its presence in the skeletal tissue and liver. Acute oral toxicity of ammonium phosphatides is low and no adverse effects were observed in a 90‐day rats study. The Panel considered that ammonium phosphatides did not raise concern for genotoxicity. The Panel identified no observed adverse effect levels (NOAELs) of 8, 500 and 3, 000 mg/kg bw per day, the highest doses tested, from dietary chronic and carcinogenicity studies with ammonium phosphatides in mice and rats, respectively. No effects on reproduction and development were observed in a dietary two‐generation reproductive toxicity study at the only dose tested of 3, 000 mg/kg bw per day, and in addition, no maternal or developmental effects were recognised in a dietary prenatal developmental toxicity study up to a dose of 4, 774 mg/kg bw per day. Based on the available toxicological database, the Panel concluded that there is no reason to revise the current ADI for ammonium phosphatides of 30 mg/kg bw per day. Considering that the ADI is not exceeded in any population group, the Panel also concluded that the use of ammonium phosphatides (E 442) as a food additive, at the permitted or reported use and use levels, would not be of safety concern.